Economic Integration in East Asia: Trends, Prospects, and a Possible Roadmap - Pradumna B. Rana (Asian Development Bank (ADB), 2006)
This paper reviews trends in East Asian regionalism in the areas of trade and investment, money and finance, and infrastructure. It presents various measures of trade and financial integration. An important finding of the paper is that increasing trade and financial integration in the region is now starting to lead to a synchronization of business cycles in a selected group of countries, further enhancing the case for monetary integration among these countries. The paper also outlines a roadmap for East Asian integration.
hdl:11540/1880
Keywords: F15; F33; F36; 330; ASEAN/East Asian economic cooperation and integration; business cycle synchronization; free trade agreements; policy coordination